Pengaruh Iklim Organisasi Dimediasi Etos Kerja terhadap Efektifitas Kerja Karyawan pada PT. XXX Bekasi - Adiningsih, Nur Fadilah; Yunita, Tyna; Jumawan, Jumawan (BUDGETING : Journal of Business, Management and Accounting, 2024)
This research aims to investigate whether the Organizational Climate influences Employee Work Effectiveness mediated through Work Ethic at PT. XXX. The study employs a quantitative method, gathering data through questionnaire distribution among 108 employees. Smart-PLS 3.0 is used for data analysis. Results indicate that, partially, organizational climate significantly affects employee work effectiveness (t-value = 2.725 > t-table = 1.96, p-value = 0.005 < 0.05). Organizational climate also influences work ethic (t-value = 11.418 > t-table = 1.96, p-value = 0.000 < 0.05). Work ethic has a significant impact on employee work effectiveness (t-value = 3.683 > t-table = 1.96, p-value = 0.005 < 0.05). The mediation of work ethic on the relationship between organizational climate and employee work effectiveness is supported (t-value = 1.945 < t-table = 1.96, p-value = 0.001 > 0.05). In summary, organizational climate a This research aims to investigate whether the Organizational Climate influences Employee Work Effectiveness mediated through Work Ethic at PT. XXX. The study employs a quantitative method, gathering data through questionnaire distribution among 108 employees. Smart-PLS 3.0 is used for data analysis. Results indicate that, partially, organizational climate significantly affects employee work effectiveness (t-value = 2.725 > t-table = 1.96, p-value = 0.005 < 0.05). Organizational climate also influences work ethic (t-value = 11.418 > t-table = 1.96, p-value = 0.000 < 0.05). Work ethic has a significant impact on employee work effectiveness (t-value = 3.683 > t-table = 1.96, p-value = 0.005 < 0.05). The mediation of work ethic on the relationship between organizational climate and employee work effectiveness is supported (t-value = 1.945 < t-table = 1.96, p-value = 0.001 > 0.05). In summary, organizational climate affects employee work effectiveness, organizational climate influences work ethic, work ethic affects employee work effectiveness, and the mediating role of work ethic in the relationship between organizational climate and employee work effectiveness is established. Keywords: , Employee Work Effectiveness, Organizational Climate, Work Ethic. ffects employee work effectiveness, organizational climate influences work ethic, work ethic affects employee work effectiveness, and the mediating role of work ethic in the relationship between organizational climate and employee work effectiveness is established. Keywords: , Employee Work Effectiveness, Organizational Climate, Work Ethic.